2021
DOI: 10.3390/atmos12060768
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of the Airborne Ambient Soot Predominant Emission Sources Determined by Raman Microspectroscopy and Thermo-Optical Method

Abstract: Raman microspectroscopy and thermo-optical-transmittance (TOT) method were used to study airborne ambient soot collected at the suburban air monitoring station in southern Poland during the residential heating (January-February) and non-heating (June–July) seasons of 2017. Carbonaceous material constituted on average 47.2 wt.% of PM2.5 during the heating season and 26.9 wt.% in the non-heating season. Average concentrations of OC (37.5 ± 11.0 μg/m3) and EC (5.3 ± 1.1 μg/m3) during the heating season were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…A study of the airborne ambient soot (PM 2.5) collected at suburban air monitoring stations in southern Poland (Silesia province) revealed that the ID/IG area ratio is distinctly higher for samples from the heating season than for these from the non-heating part of the year, mirroring the ID/IG ratio for soot originating from coal combustion and wood burning. On the other hand, values for the non-heating season samples are close to the ID/IG area ratio of diesel soot [60]. In the case presented, the anthropogenic particles observed on the black crust surface, including soot, have been deposited over an extended period, most likely since the last major conservation campaign in the 1970s.…”
Section: Discussionsupporting
confidence: 72%
“…A study of the airborne ambient soot (PM 2.5) collected at suburban air monitoring stations in southern Poland (Silesia province) revealed that the ID/IG area ratio is distinctly higher for samples from the heating season than for these from the non-heating part of the year, mirroring the ID/IG ratio for soot originating from coal combustion and wood burning. On the other hand, values for the non-heating season samples are close to the ID/IG area ratio of diesel soot [60]. In the case presented, the anthropogenic particles observed on the black crust surface, including soot, have been deposited over an extended period, most likely since the last major conservation campaign in the 1970s.…”
Section: Discussionsupporting
confidence: 72%
“…The most significant portion of airborne PM is carbon-containing materials with various physical and chemical characteristics, which account for around 20-50% of the mass concentration of PMs [59,60]. The PM-bound total carbon (TC) can be divided into two types, including organic carbon (OC) and black carbon (BC) or elemental carbon (EC).…”
Section: Carbonaceous Nanoaerosolmentioning
confidence: 99%